Change of heart : a novel - Ballard, Falon (G. P. Putnam's Sons, 2025)
Campbell Andrews despises exactly three things in life: incompetence, tardiness, and love stories. Making partner at her law firm at thirty-four, she has no time for anything or anyone else. And certainly no respect for those who choose love over work. That is, until she wakes up in Heart Springs -- her own personal hell. The good news? She's not dead. She's been magically transported to a small town straight out of the Hallmark channel, complete with a meddling mayor, seasonal festivals, and friendly townsfolk. Cam can't stand it, but in order to make it back to her real life, she has to fulfill three tasks... foremost among them, experience true love. It seems impossible. But anything's possible with a change of heart.